Dampak Kebijakan Pendapatan dan Laba Terhadap Biaya Admin: Survei pada Seller Shopee - Irine Mei Hapsari; Aris Eddy Sarwono (Universitas Warmadewa, 2024)
This study analyzes the impact of Shopee's administrative fees on revenue and profits policies of sellers in Indonesia's e-commerce ecosystem. The research investigates how sellers adjust their pricing strategies, sales volumes, and operational efficiencies in response to the platform's administrative fees. Employing a quantitative approach with survey methodology, the study targets active Shopee sellers meeting specific criteria, such as a minimum of one year of activity and at least 100 transactions in the last six months. The findings reveal that Shopee's revenue policy has a significant positive influence on administrative fees, while sellers' profit levels demonstrate a significant negative effect. Simultaneously, both factors exhibit a substantial impact on the administrative fees borne by sellers, explaining 28.5% of the variation. This research contributes valuable insights into the relationship between administrative fees and sellers' financial performance, which can benefit e-commerce businesses, policymakers, and the platforms themselves. The study suggests that Shopee should re-evaluate its administrative fee structure, considering its impact on seller profitability. Furthermore, efforts to enhance sellers' operational efficiency through training and technological support could prove mutually beneficial.